Non‐isolated high‐voltage gain dual‐input DC/DC converter with a ZVT auxiliary circuit. Issue 4 (1st April 2019) - Zhu, Binxin; Zeng, Qingdian; Vilathgamuwa, Don Mahinda; Li, Yang; She, Xiaoli
Abstract : A non‐isolated high‐voltage gain dual‐input DC/DC converter with a zero voltage turn‐off (ZVT) auxiliary circuit has been presented. Two photovoltaic (PV) modules can be connected to the proposed converter with separate maximum power point tracking (MPPT). The cost of whole PV power generation system can be decreased significantly as a single converter is employed instead of two converters. All switches can achieve ZVT by an auxiliary circuit, and turn‐off switching losses can be decreased and the efficiency of the converter can be improved. Working principle and performance characteristics of the proposed converter are analysed in detail, a dual‐input maximum power point tracking control algorithm has been designed for the proposed converter. An 800 W experimental prototype has been built to verify the theoretical analysis.